IMPLEMENTASI ALGORITMA DIJKSTRA UNTUK MENENTUKAN JALUR TERPENDEK WILAYAH PISANGAN DAN KAMPUS NUSA MANDIRI TANGERANG (Jurnal Pilar Nusa Mandiri, 2017)
Congestion in Tangerang has become a daily sight. Many steps have been taken by the government to overcome congestion. However, congestion still happens. Therefore road users must find their own way to solve the problem. One effective way is to find the shortest alternative route that can be traversed by using Dijkstra Algorithm. The use of Dijkstra's Algorithm can provide a solution because Dijkstra's algorithm gives the output of the fastest and shortest path from the origin to the destination.
Keywords: Algoritma Dijkstra; Implementasi Rute tercepat.; Jalur Tercepat